2010
DOI: 10.1152/jn.00393.2010
|View full text |Cite
|
Sign up to set email alerts
|

Repetition Suppression Dissociates Spatial Frames of Reference in Human Saccade Generation

Abstract: Van Pelt S, Toni I, Diedrichsen J, Medendorp WP. Repetition suppression dissociates spatial frames of reference in human saccade generation. J Neurophysiol 104: 1239 -1248. First published June 30, 2010 doi:10.1152/jn.00393.2010. The path from perception to action involves the transfer of information across various reference frames. Here we applied a functional magnetic resonance imaging (fMRI) repetition suppression paradigm to determine the reference frame(s) in which the cortical activity is coded at sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 69 publications
(75 reference statements)
5
29
1
Order By: Relevance
“…In comparison, evidence suggests that the FEF and IPS contain a salience map in gaze-centered coordinates that helps guide exploration of the visual environment (16,30,31), consistent with our mapping of the FEF-IPS2 pathway. In addition to using the FEF-IPS2 and SEF-SPL1 pathways to guide eye movements and provide attentional feedback to sensory areas, these pathways may act in concert to remap space across saccades, considering that the relative positions of objects and viewer-centered information help maintain visual stability (32).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In comparison, evidence suggests that the FEF and IPS contain a salience map in gaze-centered coordinates that helps guide exploration of the visual environment (16,30,31), consistent with our mapping of the FEF-IPS2 pathway. In addition to using the FEF-IPS2 and SEF-SPL1 pathways to guide eye movements and provide attentional feedback to sensory areas, these pathways may act in concert to remap space across saccades, considering that the relative positions of objects and viewer-centered information help maintain visual stability (32).…”
Section: Discussionsupporting
confidence: 86%
“…S1; refs. [14][15][16]. Macaque SEF also lacks a clear topography (17,18), although macaque SEF neurons have been shown to represent space in gaze-centered as well as head-, body-, and objectcentered reference frames (9,19).…”
mentioning
confidence: 99%
“…Future work will need to differentiate between these various possibilities. Interestingly, a recent study using fMRI repetition suppression found similar evidence for a clear retinotopic representation in all studied regions, but on top of that, weaker evidence for nonretinal coding were also found in the IPS (Van Pelt et al 2010).…”
Section: Discussionmentioning
confidence: 70%
“…The contrast of interest was computed for each unilateral ROI as the sum of the two regressors capturing saccade planning to an updated target presented within the contra-illusion (i.e., the L-illusion for the right hemisphere and the R-illusion for the left hemisphere) minus the sum of the two regressors capturing saccade planning to an updated target within the ipsi-illusion (i.e., the R-illusion for the right hemisphere and the L-illusion for the left hemisphere). Next, to assess whether the BOLD response during the delay was lateralized as a result of the illusion, we computed a contralateral bias C that scales the contrast to the sum of the BOLD response (e.g., Schluppeck et al, 2006;Van Pelt et al, …”
Section: General Linear Model and Regions Of Interestmentioning
confidence: 99%